2011
DOI: 10.4038/cjsbs.v39i2.2995
|View full text |Cite
|
Sign up to set email alerts
|

<i>Taruga</i> (Anura: Rhacophoridae), a new genus of foam-nesting tree frogs endemic to Sri Lanka

Abstract: Phylogenetic relationships among foam-nesting clades of Old World tree frogs are analyzed using both nuclear and mitochondrial DNA data, with particular focus on Sri Lankan members of the genus Polypedates. A distinctive, highly supported endemic Sri Lankan clade is identified, and recognized as a new genus, Taruga. This clade, which had previously been assigned to the genus Polypedates, includes P. eques, P. fastigo and P. longinasus. A combination of characters distinguishes adult Taruga from Polypedates: Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Whenever possible, samples from the type localities of nominal taxa were included and multiple samples were used to represent widespread species. Currently, 15 genera with 321 species of rhacophorids are recognized (25,47). The mitochondrial DNA (mtDNA) dataset included 317 samples from all 15 rhacophorid genera, representing 114 species.…”
Section: Methodsmentioning
confidence: 99%
“…Whenever possible, samples from the type localities of nominal taxa were included and multiple samples were used to represent widespread species. Currently, 15 genera with 321 species of rhacophorids are recognized (25,47). The mitochondrial DNA (mtDNA) dataset included 317 samples from all 15 rhacophorid genera, representing 114 species.…”
Section: Methodsmentioning
confidence: 99%
“…These new generic descriptions are largely based on molecular data and to a lesser extent on molecular data and morphology [13,14,16]. One of the main impediments to new lineage identification, prior to the advent of molecular phylogenetic techniques, was the lack of consistent external morphological characters.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main impediments to new lineage identification, prior to the advent of molecular phylogenetic techniques, was the lack of consistent external morphological characters. In recent phylogenetic reconstructions of rhacophorid relationships, adult skeletal data have been sparsely used [13,14], but never skeletal ontogeny.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bossuyt et al (2004), in an analysis of several vertebrate (shrub frogs, caecilians, earth snakes and freshwater fish) and invertebrate (freshwater crabs and shrimps) groups representing a diversity of lifehistory strategies showed that the wet-adapted taxa are characterized by clade level endemism. For wet-adapted frogs, this notion was reinforced with the recognition of a Sri Lankan endemic genus, Taruga, (Meegaskumbura et al, 2010), delineation of reciprocal endemicity of Hylarana species of India and Sri Lanka (Biju et al, 2014), endemicity of Nannophrys (which exhibits several unique features , and the endemicity of the genus Adenomus Van Bocxlaer et al, 2009). However, it is not known if this pattern is representative of the other anuran taxa, especially for some of the dry-adapted species, which are putatively shared with India.…”
Section: Introductionmentioning
confidence: 99%